Existência e multiplicidade de soluções para uma classe de problemas quaselineares envolvendo expoentes variáveis - Barreiro, José Lindomberg Possiano (2014)
In this work, we will use the Mountain Pass Theorem for an even Functional, Genus Theory, Ekeland's variational principle and some properties involving Nehari manifolds to obtain existence and multiplicity of solutions for the following class of quasilinear problems involving variable exponents 8<: p(x)u + jujp(x)2u = f(x; u); x 2 u 2 W1;p(x) 0 ( ) n f0g where is a bounded domain in RN, not necessarily bounded, p(x) is the p(x)-Laplacian operator given by p(x)u = divjrujp(x)2ru; p: ! R and f : R ! R are continuous functions satisfying certain conditions, which will specified be later on.